Strategic customer management integrating relationship marketing and CRM - Payne, Adrian, 1945-; Frow, Pennie (Cambridge University Press, 2013)
"The first textbook to integrate relationship marketing and CRM. Case studies from around the world connect theory with global practice."
Keywords: řízení vztahů se zákazníky; marketing; customer relationship management; učebnice; případové studie; elektronické knihy; textbooks; case studies; electronic books